The standard equation of a circle is expressed as:
Given a circle whose equation is
Get the centre of the circle
2gx = -2x
2g = -2
g = -1
Similarly, 2fy = 0
f = 0
Centre = (-(-1), 0) = (1, 0)
This shows that the center of the circle lies on the x-axis
r = radius = √g²+f²-C
radius = √1²+0²-(-8)
radius =√9 = 3 units
The radius of the circle is 3 units.
For the circle x² + y² = 9, the radius is expressed as:
r² = 9
r = 3 units
Hence the radius of this circle is the same as the radius of the circle whose equation is x² + y² = 9.
Learn more on circles here: brainly.com/question/23226948
Answer:
a, b and e
Step-by-step explanation:
i got it correct on edge
Answer:
Step-by-step explanation:
If a cubes diagonal measures you can solve for its sidelength by creating a triangle. Visualize the diagonal as the hypotenuse of our triangle inside the cube. Then, one of the legs would be the side of the cube itself, and the other leg would be the diagonal of the bottom side of the cube. Knowing this is a cube, we can call each side s. If each side is s, then the diagonal of the bottom face is ( this is a special triangle property, triangle.) Then we know our triangle is a right triangle, so we can use the Pythagorean theorem to solve for s.
Solve this equation for s.
Since we now found the side length of the cube, we can find its volume by cubing the side length: